The use οf νiruses for controlling pest species οf insects - Moore, N.F.; Manousis, T. (ENTOMOLOGIA HELLENICA, 1986)
Insect viruses have been used effectively to control pest species of insects. While viruses from several families have been used, members of the Baculoviridae have proven most successful. The successful viruses are mentioned and a brief introduction into insect virus identification is followed by sufficient detail to differentiate between the major groups of viruses which have been used as field control agents. References are minimised to recent key articles on all the families of viruses found in insects.